The Influence of Work Environment, Job Satisfaction and Work Commitment on the Performance of Jombang Regency Agriculture Service Employees - Lia Firdia Fitriani; Taqiyuddin, Akhmad; Sa'adah , Lailatus (Jurnal Ilmiah Ekonomi Global Masa Kini, 2024)
The aim of this research is to determine the influence of the work environment, job satisfaction and work commitment on the performance of Jombang Regency Agriculture Service employees. The research method used is a quantitative approach, used to test a population or sample, the data is analyzed statistically, the aim is to test the hypothesis being developed. The type of research carried out by the author uses associative research. This research is used to determine whether there is an influence or relationship between the targeted variables. This research can build a theory that can function to explain, predict and control a symptom. The sampling technique is a retrieval technique. To determine the sample to be used in research, various sampling techniques are used. Non-probability sampling A sampling technique that does not provide an equal chance for each element or member of the population to be selected as a sample. The sample technique for this research uses total/census sampling, a sample return technique where all members are collected and used as samples as subjects studied or as respondents providing information. The sample taken in this research amounted to 64 respondents.  Data collection techniques using observation, documentation and distributing questionnaires directly, then processed using SPSS for Windows version 26. The research results from this study show that the work environment has a positive and significant effect on employee performance, job satisfaction does not have a positive and significant effect on employee performance and work commitment has a positive and significant effect on employee performance. Keywords: work environment, job satisfaction, work commitment, employee performance